Urban agriculture as a food resource in developing countries (Journal of the College of Basic Education, 2024)
More than half of the world's population now lives in cities and in many developing countries, the urbanization process is consistent with increasing poverty in urban areas, a polluted environment, growing food in security, malnutrition, especially for children, pregnant and lactating women, and increasing unemployment. Urban agriculture represents an opportunity to improve food supply, health conditions, the local economy, social integration and overall environmental sustainability. Urban agriculture is found around the world in a variesty of agricultural systems. Worldwide, 25-30% of the urban population is involved in the agri-food sector and urban agriculture will gain recognition for its benefits and services due to the growing urban population and rural-urban migration. The actual scarcity of knowledge related to urban agriculture has somewhat hampered the importance of this activity. We review the social, cultural, technical, economic, environmental and political factors that influence urban agriculture with examples taken from East Asia, South America or East Africa and discuss the definition of urban agriculture, its benefits and limitations. The food security benefits of urban agriculture are evident in the fact that 100 to 200 million urban farmers worldwide supply fresh horticultural goods to city markets.Urban agriculture favors social improvement as the poor spend up to 85% of their income on purchasing food and most urban farmers belong to the poorest population. Socially, urban agriculture supports social inclusion and reduces gender inequality, as 65% of urban farmers are women. Urban agriculture has cross-benefits through reducing urban waste, improving urban biodiversity and air quality, and, in general, reducing environmental impact. related to food transportation and storage. The production of horticultural goods shows the main benefits of urban agriculture. Fruit and vegetable crops give high yields of up to 50 kilograms per square meter per year, more efficient use of agricultural inputs, high added value, and highly perishable products that can easily replace rural production in the local market. Urban horticulture is the branch Most competitive for urban agriculture due to the high cost of urban land and the need for high efficiency in water and fertilizer use. Traditional urban gardening systems are classified into four types: allotment gardens, family gardens, simplified extensive systems, shifting cultivation, and intensive systems. We also describe innovative systems including organic farming and simplified soilless farms.